The Beauty of and Barriers to Organizational Theories of Identity - Pratt, Michael G.; Foreman, Peter O. (Academy of Management Review, 2000)
The article presents a commentary on this special edition of “Academy of Management Journal” by two of the authors of one of the articles. The authors discuss the difficulties and beauties of the diversity of definitions of identity, identification, and image. The article discusses the plurality of identity, multiple identity management, and identity and power. The challenges in the field are identified as delineating the origin of the identity, naming identity claimants, delineating the identity audience, and being aware of time.